Analisis perhitungan harga pokok penjualan meter pascabayar dan meter prabayar dalam menggunakan metode variable cost pada PT. PLN (Persero) ULP Manado Selatan - Rianto, Rifka Sharen; Karamoy, Herman; Wangkar, Anneke (Universitas Sam Ratulangi, 2019)
Pln company, which means a state-owned electricity company, in which this state-owned company has a meter product that helps the public to supply electricity, but in determining the selling price of the meter products orten experience problems because the selling price of the meter products often changes making customers often make complaints towards the company, for that the authors aim to examine the cost of goods sold in the company by using the variabel cost method, the study was conducted using a type of qualitative data to analyze accounting treatment and for the calculation of the author using quantitative data in the form of financial statements in order to calculate the calculation of cost of goods sold, after analysis by using the varibel cost method, the authors get the results under the calculation of variabel cost more profitable and not harming customers or costs that are not interested in calculating the cost of goods sold is the final result of the process of calculating the cost of goods sold of a postpaid meter product and a prepaid meter using the Variable cost method. There are 2 major groups in each sales process that will form the cost of goods sold report, namely production costs and non-production costs. PT. PLN (Persero) ULP Manado Selatan which is the object of research has a calculation of cost of goods in postpaid and prepaid meter products. In the calculation of the company's cost of goods sold is very high for the emphasis on the cost of products that cause very high cost problems, therefore according to the discussion to solve a problem in the calculation of cost of goods sold, the authors use the cost of goods sold calculation with the variable cost method. After recalculation using the variable cost method, the results obtained are lower than the calculation by the company, where the cost of selling postpaid and prepaid meters is lower, the difference is caused by excess loading of costs that should not be included in the cost of goods sold.